2022
DOI: 10.1128/cmr.00338-20
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on the Role of the Gut Microbiome in Human Neurological Disorders

Abstract: The human body is full of an extensive number of commensal microbes, consisting of bacteria, viruses, and fungi, collectively termed the human microbiome. The initial acquisition of microbiota occurs from both the external and maternal environments, and the vast majority of them colonize the gastrointestinal tract (GIT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
126
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(165 citation statements)
references
References 458 publications
3
126
0
1
Order By: Relevance
“…The gut microbiome differs from individual to individual, and the composition of the microbiota is believed to affect various metabolic disorders, such as obesity, hyperglycemia, and dyslipidemia, which are risk factors for type 2 diabetes, hepatosteatosis, and arteriosclerosis [404]. Reduced diversity of gut microbiota has been linked with various pathophysiological conditions, such as depression, schizophrenia, neurological disorders, and chronic fatigue [405][406][407][408][409]. Microbiota can affect the endocannabinoid system and the nervous system, and vice versa; the nervous system and the endocannabinoids can influence the enteric microbiota composition [112,285,390,397,410,411].…”
Section: Dialog Between the Gut Microbiota And The Endocannabinoid Sy...mentioning
confidence: 99%
“…The gut microbiome differs from individual to individual, and the composition of the microbiota is believed to affect various metabolic disorders, such as obesity, hyperglycemia, and dyslipidemia, which are risk factors for type 2 diabetes, hepatosteatosis, and arteriosclerosis [404]. Reduced diversity of gut microbiota has been linked with various pathophysiological conditions, such as depression, schizophrenia, neurological disorders, and chronic fatigue [405][406][407][408][409]. Microbiota can affect the endocannabinoid system and the nervous system, and vice versa; the nervous system and the endocannabinoids can influence the enteric microbiota composition [112,285,390,397,410,411].…”
Section: Dialog Between the Gut Microbiota And The Endocannabinoid Sy...mentioning
confidence: 99%
“…The overall goals of these strategies are that the support and maintenance of cytoskeletal structures essential for synaptic plasticity may more effectively manage the many neurological diseases in which NF-L gene expression and abundance play a determinant and defining role. Lastly, dietarybased modifications of microbial dysbiosis may be an attractive means to modify the abundance, speciation, and complexity of enterotoxigenic forms of AD-relevant microbes and their potential for the pathological discharge of highly neurotoxic microbial-derived secretions that include LPS (4, 50,[53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have reported that specific drugs may affect the gut microbiome ( 24 ) and may also affect the host through microbial metabolism ( 25 27 ). In the course of studying this cohort of 118 preterm infants, we found the following interesting links between aminophylline, FI events, and the gut microbiome.…”
Section: Discussionmentioning
confidence: 99%